STEM-42. GENOME-WIDE CRISPR SCREENS IN BRAIN TUMOR INITIATING CELLS (BTICS) IDENTIFY POTENT SENSITIZERS OF CONVENTIONAL CHEMORADIOTHERAPY. (6th November 2017) - Chokshi, Chirayu; Tieu, David; Vora, Parvez; Venugopal, Chitra; Chan, Katherine; Tong, Amy; Brown, Kevin; Singh, Mohini; Moffat, Jason; Singh, Sheila
Abstract: Glioblastoma (GBM) is a highly aggressive and most common form of malignant primary brain tumor in adults (WHO grade IV). Despite surgical and adjuvant therapeutic interventions, including chemotherapy with the alkylating agent TMZ and cranial irradiation, GBM relapse is inevitable with a median survival of <15 months. Extensive intratumoral heterogeneity (ITH) in GBM is believed to be the leading cause of therapy resistance and disease relapse, suggesting that therapy acts as a selection pressure or bottleneck for tumor evolution from minority cell populations present at time of initial diagnosis. Recently, the advent of CRISPR-Cas9 technology has led to the development of genome-wide libraries of sgRNAs capable of introducing insertion-deletion (indels) within exons, leading to a frameshift mutation two-thirds of the time. Here, we present the first genome-wide CRISPR-Cas9 knockout screen in patient-derived GBM BTICs aimed to discover synthetic lethal sensitizers of conventional chemoradiotherapy. Briefly, we performed genome-wide CRISPR-Cas9 screens in treatment-naïve GBM BTICs subjected to in vitro chemotherapy with TMZ and irradiation. By comparing sgRNA dynamics at each doubling period, we were able to identify potent sensitizer genes exclusive to combined chemoradiotherapy, and not TMZ or irradiation alone. Candidate sensitizer genes were validated in an arrayed format to evaluate impact on GBM BTIC self renewal, proliferation, and sensitivity to TMZ and radiation. We aim to further validate these sensitizers of conventional chemoradiotherapy by performing a focused CRISPR-Cas9 genetic screen in our patient-derived xenograft model of treatment-refractory GBM. Ultimately, adjuvants targeting sensitizer genes could greatly enhance the impact of conventional chemoradiotherapy in GBM patients, leading to an increase in patient survival.